The use of near-infrared spectroscopy (NIRS) in the physiological assessment of sprint triathlon - Butson, J. (School of Sport, Rehabilitation & Exercise Sciences, University of Essex, 2020)
Sprint triathlon is a high intensity endurance discipline with ever-growing participation rates, butthe sportcurrently remains under researched. The requirement to complete swim, cycle and run stages consecutively places unique physiological demands upon triathletes that are superiorto that ofcompleting identicaldistances singularly. Despite the knowledge that sprint triathlon is greater than the sum of its parts, the inclusion of all three disciplines in triathlon research is rare.A review of the literature identified a wide variety of measurement tools that have been utilised to observe the global physiological responses (oxygen consumption, heart rate, blood lactate concentration among others)that occur during participation. Despite this wealth ofinformation, it is complex to piece together the findings into a larger picture of performance, with a particular lack of swimming related research. A single study from the review looked to utilise Near-Infrared Spectroscopy (NIRS) within triathletes. NIRS is a light-based technology that reports on the relationship between oxygen delivery and utilisationat the siteof gas exchange in the muscle, a key indicator of performance in aerobic events such as sprint triathlon. A laboratory based experimental study explored the utility of multi-site NIRS as a measurement tool within triathlon using recreational male triathletes (n=11). A comprehensive profile of global and peripheral responses across the triathlon simulation was created, identifying the measures associated with performance. NIRS yielded different oxygenation responses between upper and lower limbs throughout and identified a greater peripheral measurement variability between participants compared to global physiological measures. It is suggested this variability highlights differences in efficiency between athletes, although no direct correlations were found between NIRS data during swim, cycle and run and overall performance. As a measurement tool NIRS has the potential to increase the specificity of physiological information available when creating strategies to be applied in sprint triathlon training and competition.